Linguistic and economic capital in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau wisely looks to mainland China, South-East Asia, and Portuguese-speaking countries, as part of its economic diversification. However, to be a player on the international stage and world-wide market, it must look wider, and, hence, the standard of English in Macau must improve dramatically and urgently.
Section: MAG